2008
DOI: 10.1097/01.ncc.0000305758.66238.a1
|View full text |Cite
|
Sign up to set email alerts
|

Crying in Solitude or With Someone for Support and Consolation-Experiences From Family Members in Palliative Home Care

Abstract: Crying has not been studied from the perspective of family members of patients in palliative care. The aim of this study was to explore the significance of family members crying in a palliative care context with special reference to factors that influence crying. Interviews were carried out with 14 family members of patients admitted to palliative care. A hermeneutic approach according to Gadamer was used. Three main categories emerged. (1) Before the start of crying, some prerequisites for crying had to be fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Family members tried to hide their crying in front of the ill family member to ease the burden. Crying as an emotion can be expressed as being shared with someone for support and consolation or escape to solitude for integrity and respite (Rydé, Strang, & Friedrichsen, 2008). Family members also took on responsibility and felt they were supposed to watch over the ill family member 24 hours a day (Efraimsson, Höglund, & Sandman, 2001), a practice that did not give any time for themselves (Bäckström & Sundin, 2009;Munck et al, 2008;Ziegert, Fridlund, & Lidell, 2009).…”
Section: Family Members Feelings and Experiences Of Family Lifementioning
confidence: 99%
“…Family members tried to hide their crying in front of the ill family member to ease the burden. Crying as an emotion can be expressed as being shared with someone for support and consolation or escape to solitude for integrity and respite (Rydé, Strang, & Friedrichsen, 2008). Family members also took on responsibility and felt they were supposed to watch over the ill family member 24 hours a day (Efraimsson, Höglund, & Sandman, 2001), a practice that did not give any time for themselves (Bäckström & Sundin, 2009;Munck et al, 2008;Ziegert, Fridlund, & Lidell, 2009).…”
Section: Family Members Feelings and Experiences Of Family Lifementioning
confidence: 99%
“…The need for finding and reconstructing meaning related to the present condition was also a significant finding in these studies. Ryde et al 35 in their study made clear that family members of patients admitted to palliative care tried to do the best possible by adopting or hiding their crying to ease the patient's burden and to create a positive counterbalance to suffering and grief. For example, Kruszewski 29 found that for parents who terminated a pregnancy for fetal anomaly, despite ongoing feeling of loss and regret, coping processes such as decision making, transforming, constructing a cause, reconstructing meaning, backgrounding, displacing blame, and reconstructing one's moral code are noted among the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The interview guide used contained background questions, questions about situations where patients cry, which strategies the nurse used and how support can be given in these situations, and what hinders or facilitates the possibility of providing good support in crying situations. The interview guide was developed based on previous studies (Rydé et al , 2007; 2008). The interviews, which lasted between 15 and 30 min, were tape-recorded and transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
“…Crying has many dimensions and may be viewed primarily as an expression of grief and loss, as well as a call for attention and a way of communicating both anger and joy (Frijda, 1986). There are few studies on this subject of crying in palliative care (Rydé et al 2007(Rydé et al , 2008 although there is a need for emotional support in situations of severe loss and death (Skilbeck and Payne, 2003). There is also a need to provide information and practical help to patients and their friends and relatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation